(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
English Language Learners (ELL) are one of the fastest growing subgroups in the classroom today, and the knowledge gap between ELL students and native language speakers grows wider. Vocabulary comprehension is becoming a deep-rooted problem in many classrooms; therefore, it is important to identify ways to accurately assess an ELL student’s vocabulary knowledge and retention. A variety of assessment styles and tools should be utilized in the classroom to better reflect an ELL student’s vocabulary knowledge and growth. There are five alternative assessment styles teachers should consider when choosing tests in the classroom: formative, performance, quality reviews, badges and micro credentials, and multiple measures. Educators face challenges of learning what assessment will best suit a standard and a student’s abilities. As future generations present educators with learning challenges, these five assessment styles can provide teachers with a richer understanding of their ELL students’ capabilities and retention.